Diagnosis and Prognosis in Sudden Cardiac Arrest Survivors Without Coronary Artery Disease: Utility of a Clinical Approach Using Cardiac Magnetic Resonance Imaging. (December 2017) - Rodrigues, Patricia; Joshi, Abhishek; Williams, Howell; Westwood, Mark; Petersen, Steffen E.; Zemrak, Filip; Schilling, Richard J.; Kirkby, Claire; Wragg, Andrew; Manisty, Charlotte; Mohiddin, Saidi
Abstract : Background—: Determining the pathogenesis of sudden cardiac arrest or periarrest without significant coronary artery disease is crucial for management and prognosis. Cardiovascular magnetic resonance (CMR) can detect morphological, functional, or tissue abnormalities, and we sought to evaluate the role of CMR in determining sudden cardiac arrest pathogenesis and prognosis in survivors. Methods and Results—: We retrospectively reviewed cardiac investigations and clinical outcomes in consecutive survivors of potentially fatal arrhythmias without coronary artery disease admitted to our institutions from 2008 to 2014. After coronary angiography and echocardiography, all underwent CMR and, when indicated, electrophysiology studies. Major adverse cardiac events (MACE), comprising significant nonfatal ventricular arrhythmia or death, was the primary outcome. Of 164 included subjects (65% men; mean age 48 [18–80] years), CMR contributed to the diagnosis in 80 (49%) and was decisive in 50 cases (30%). Dilated cardiomyopathy (n=27), myocarditis or sarcoidosis (n=22), occult myocardial infarction (n=13), and hypertrophic cardiomyopathy (n=9) were most frequent. Arrhythmic causes were found in 14% while no cause was identified in 36%. MACE occurred in 31% of subjects during a median follow-up of 32 months. MACE associated with presence of a CMR diagnosis, extent of late gadolinium enhancement, and left and right ventricular ejection fractions. Right ventricular ejection fraction was an independent predictor of MACE. Conclusions—: CMR identified a likely pathogenesis for sudden cardiac arrest in nearly half of survivors in whom coronary artery disease had been excluded. One in 3 subjects had MACE; risk doubled in those with a CMR diagnosis and some CMR parameters—late gadolinium enhancement, left ventricular ejection fraction, and especially right ventricular ejection fraction—associated with prognosis. Abstract : Supplemental Digital Content is available in the text.